Ultrasound guided percutaneous central venous catheters in neonatal intensive care unit - Ateş, Ufuk; Derme, Turan; Yılmaz, Yavuz; Özkan-Ulu, Hülya; Canpolat, Fuat Emre (The Turkish Journal of Pediatrics, 2018)
Central venous catheters can be life-saving, especially in very low birth weight and sick newborns for whom peripheral access is difficult. However, the placement of a central venous catheter is technically difficult, especially in premature and newborn infants. To demonstrate the efficacy of placement of central venous catheters under guidance of ultrasonography (US) in neonatal intensive care units. The patients who were hospitalized in newborn intensive care unit and central venous catheters were placed into the internal jugular vein under the guidance of US were analyzed retrospectively. Successful cannulation rate was 90.9% in patients. The rate of success at first attempt was 68.1% in patients. The rate of three and more attempts was 9.1% in patients. The rate of complication was 9.1% in patients. The average intervention time was 8 minutes in patients. Central venous cannulation under the guidance of two-dimensional US is an effective method which can be easily and safely applied to low birth weight premature and newborn infants in newborn intensive care units.
Keywords: central venous catheterization; newborn; ultrasound